Tandem [4 + 2]/[2 + 2] cycloaddition reactions involving indene or benzofurans and arynes - Bhojgude, Sachin Suresh; Thangaraj, Manikandan; Suresh, Eringathodi; Biju, Akkattu T. (Organic Letters, 2014)
The reaction of arynes with indene/benzofurans has been developed. The arynes were generated from 2-(trimethylsilyl)aryl triflates by the fluoride-induced 1,2-elimination react with indene or various benzofurans proceeding via a cascade reaction involving the Diels–Alder reaction and a [2 + 2] cycloaddition reaction. The tandem process afforded functionalized dihydrobenzocyclobutaphenanthrenes in moderate to good yields. Moreover, the method has been utilized for the one-pot synthesis of benzo[b]fluoranthene.